FINANCIAL DISTRESS PREDICTION USING ALTMAN MODEL (CASE STUDY: PT. X) - Mulyana Muslihat, Rahmat
Now Indonesia is experiencing rapid industrial development, one of them is industry 4.0. Industry 4.0 will bring to changes and innovations in the business sector to become more efficient and effective, to support the development of industry 4.0 investment is needed one of them in the telecommunications infrastructure sector because of that the company which will become a research topic is one of the telecommunications infrastructure companies in Indonesia. To prepare for the development of industry 4.0 the company must be able to survive in the changes in the industry. Therefore, one of the supporting factors so that the company can survive is to have a healthy financial condition. After seeing the annual reports, it can be seen that within five years it turns out that the net profit earned by PT. X has increased and decreased and also the growth of current assets and short-term debt is not comparable, this can be used as an indication of financial problems that occur in the company.